Analysis of the vulnerability of college students to HIV/AIDS - Elys Oliveira Bezerra; Ana Clara Patriota Chaves; Maria Lúcia Duarte Pereira; Flaviana Ribeiro Gomes de Melo (Rev Rene)
Considering youth HIV/AIDS vulnerability, this study aims to analyze the HIV sexual transmission vulnerabilities among college students. Exploratory and quantitative research carried out on a public higher education institution in Fortaleza-CE, Brazil. The studied sample was composed by 161 students. For data collection we used a semi-structured questionnaire and a Likert attitude questionnaire, self-administrated in collective situation. Most participants were female (67.1%), sexually active (63.4%), never took an HIV test (80%). The median age at first intercourse was 17.2 years. School was mentioned as the main source of information about HIV prevention.The college students interviewed had limited knowledge on HIV prevention, favorable attitudes to condom use, low perception of the risks of having unprotected sex, besides not knowing for sure if they are not infected by HIV. Therefore, it is necessary to invest in educational campaigns on sexuality and STD/AIDS inside the university.